2004
DOI: 10.1093/brain/awh171
|View full text |Cite
|
Sign up to set email alerts
|

MyD88 is required for mounting a robust host immune response to Streptococcus pneumoniae in the CNS

Abstract: Myeloid differentiation factor 88 (MyD88) is an essential intracellular signal transducer in Toll-like receptor (TLR) and interleukin (IL)-1 receptor family member-mediated cell activation. In order to characterize the role of MyD88 in pneumococcal meningitis we used gene-targeted mice lacking functional MyD88 expression. At 24 h after intracisternal infection, MyD88- deficient mice displayed a markedly diminished inflammatory host response in the CNS, as evidenced by reduced CSF pleocytosis and expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
119
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(127 citation statements)
references
References 41 publications
6
119
0
2
Order By: Relevance
“…Moreover, we recently observed that MyD88-deficient mice had a similar phenotype to that of C3-deficient mice. Infected MyD88-deficient mice displayed an attenuated immune response and less pronounced intracranial complications, but had a higher mortality rate that was associated with more severe bacteremia, more pronounced hypothermia, more frequent breathing problems, and more pronounced secondary pneumonia (19), when compared with infected wt mice. Because MyD88 deficiency was associated with a substantial suppression of the brain expression of complement factors, it is conceivable that the absence of complement factors is responsible for the clinical phenotype observed in both mouse strains.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Moreover, we recently observed that MyD88-deficient mice had a similar phenotype to that of C3-deficient mice. Infected MyD88-deficient mice displayed an attenuated immune response and less pronounced intracranial complications, but had a higher mortality rate that was associated with more severe bacteremia, more pronounced hypothermia, more frequent breathing problems, and more pronounced secondary pneumonia (19), when compared with infected wt mice. Because MyD88 deficiency was associated with a substantial suppression of the brain expression of complement factors, it is conceivable that the absence of complement factors is responsible for the clinical phenotype observed in both mouse strains.…”
Section: Discussionmentioning
confidence: 98%
“…A well-characterized mouse model of pneumococcal meningitis was used in this study (19,27). Briefly, meningitis was induced by transcutaneous injection of 15 l of a bacterial suspension containing 10 7 CFU/ml S. pneumoniae type 3 into the cisterna magna under short-term anesthesia with halothane.…”
Section: Mouse Model Of Pneumococcal Meningitismentioning
confidence: 99%
See 3 more Smart Citations